Analisis Implementasi Metode Transportasi dalam Linier Program Menuju Efisiensi Biaya Distribusi pada UMKM Aris Cookies Jabung Ponorogo - Intan Pratiwi, Dila; Afta Ayumni Audrya, Navalya; Wahyu Diana, Angelia; Arissis Slash Axl Rose, Aldhery; Purwaningrum, Titis (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This study aims to improve the optimization of the distribution efficiency of Kue Aris UMKM in Jabung Ponorogo using the linear programming transportation method. The three techniques used are Vogel's Approximation (VAM), Least Cost (LC), and North West Corner (NWC). The results of the study indicate that the minimum distribution costs are NWC Rp1,705,000, LC Rp1,635,000, and VAM Rp1,515,000. This shows that the VAM method is the most effective in minimizing distribution costs. This study contributes to the management of goods distribution in the UMKM sector with a data-based approach and quantitative analysis.